Precarious employment as survival strategy: An emerging reality in Zimbabwean hotels - Farai Ncube (Globeedu Group, 2023)
The new modes of production and concomitant consumption patterns brought by new technology and globalization have introduced a reconfiguration of work practices, experiences and institutions that have transformed political and economic relations within and between nations. The current economic recession being experienced by Zimbabwe is not an isolated economic phenomenon but simply marks the new wave of change typifying the employment conditions world over. Numerous survival strategies adopted by most companies in Zimbabwe have rendered general corporate employment and in particular in the hotel industry chronically insecure and unstable. Employment in Zimbabwe has become precarious. Adopting the employment strain model the research revealed that hotels are adopting precarious working conditions in order to survive and ensure profitability. While such forms of employment appear manipulative on the part of the workers, employers have embraced them as a buffer inventory to insulate themselves against the negative effects of the new business reality in Zimbabwe. The research focused on three hotels based in Harare, capital city of Zimbabwe. Data was collected through interviews and questionnaires to 120 participants revealed the reality of precarious employment.